An E. coli screening machine in water via fluorescence detection - Juhong, Aniwat; Piyawattanametha, Wibool (My University, 2019)
We have developed a fluorescence based detection for rapid E. coli which is an indicator for fecal contamination for water quality. This technology has cut down the time taken to detect E. coli from a few days to just a couple of hours. The system relies on the enzyme β-D glucuronidase (GUD) reacts with 4-methylumblliferyl-β-D glucuronide (MUG) resulting in a byproduct named 4-methylumbellliferone (4MU). Our system can detect this byproduct in the concentration range from 0.01 to 80 μM which can then be enumerated to be the number of E. coli.
Keywords: Escherichia coli; Fluorescence; Optical detection; Portable detector